Antibacterial regenerated PET elastic fiber and preparation method thereof

By generating antibacterial materials by reacting the hekexamine and 1-1-1H-1H-Intidazole-2-formaldehyde reactions, and combined with modified hydrogen phosphate materials and other ingredients, composite antibacterial materials are prepared, which solves the lack of existing regeneration PET elastic fiber deficiency The problem of effective antibacterial function significantly improves the antibacterial performance and service life of fibers.

CN119372801AInactive Publication Date: 2025-01-28JIANG SU KA LE FANG XIN CAI LIAO YOU XIAN GONG SI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411633916.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing regenerated PET elastic fibers lack effective antibacterial functions and are difficult to provide sufficient health protection in the medical and health fields. Inadequate antibacterial performance leads to a shortening of product service life.

Method used

By generating antibacterial materials by reacting the hebnnamine and 1-1-1H-1H-Intidazole-2-formaldehyde reactions, and loaded it to the modified hydrogen phosphate material, combined with tethamine tetrazide sodium, bronze sulfate, and Components such as sodium hydroxide and ascorbic acid are prepared for composite antibacterial materials, and PET elastic fibers are treated through technologies such as high temperature melt, local cooling, and vacuum drying, giving it antibacterial performance.

Benefits of technology

It significantly improves the antibacterial properties of PET elastic fibers, effectively inhibit bacterial growth and reproduction, extend the service life of the product, and improve the hygiene guarantee capabilities and overall quality of fiber products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of resource regeneration, in particular to an antibacterial regenerated PET elastic fiber and a preparation method thereof. The preparation method comprises the following steps: adding hexamethylenediamine and 1-methyl-1H-imidazole-2-formaldehyde to obtain an antibacterial material; loading an antibacterial material into the modified zirconium hydrogen phosphate material to obtain a modified antibacterial material; and mixing the modified antibacterial material, disodium ethylene diamine tetraacetate, copper sulfate pentahydrate, a sodium hydroxide solution and an ascorbic acid solution to obtain the composite antibacterial material. Mixing the regenerated PET powder, a composite antibacterial material, an inorganic pigment, an auxiliary agent and propylene glycol, and performing high-temperature melting, local cooling, vacuum drying, double-helix melting, granulation and melt spinning to obtain PET elastic fibers; and finally, dipping the PET elastic fiber in the TiO2 solution to obtain a finished product. The finished product prepared by the invention has good antibacterial property and mechanical property, so that the finished product has a wide application prospect in the technical field of resource regeneration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource recycling, in particular to an antibacterial recycled PET elastic fiber and a preparation method thereof. Background Art

[0002] Recycled PET elastic fiber has multiple values ​​and wide applications, which are mainly reflected in the following aspects: First, recycled PET elastic fiber is of great significance in sustainable development. The main raw material of recycled PET elastic fiber comes from recycled PET plastic bottles. By converting waste into high-value fiber materials, it helps to reduce resource consumption and environmental pollution and promote the development of circular economy. Secondly, recycled PET elastic fiber inherits the excellent physical properties and engineering properties of PET materials. Recycled PET elastic fiber has good strength, abrasion resistance, excellent elasticity and softness, making it suitable for the manufacture of various textiles and industrial products such as clothing, furniture and car seats, thus having broad application prospects in the industrial and consumer goods markets. In addition, the production process of recycled PET elastic fiber is mature and stable, and relatively cost-effective. This makes it an important competitive force in the manufacturing cost-sensitive market, especially in the market environment where mass production and customization demand are growing, and it can provide reliable supply and excellent product performance.

[0003] In modern society, consumers are increasingly concerned about health and safety, especially in the medical and health fields. By adding antibacterial function to PET elastic fiber, the growth and reproduction of bacteria can be effectively inhibited, and the accumulation of pathogens on the fiber surface can be reduced, thereby reducing the risk of cross infection and improving the hygienic protection ability of fiber products in the fields of medical supplies, healthy homes, etc.

[0004] In addition, by improving the antibacterial properties of fiber products, the service life of the products can be effectively extended, mainly by reducing odor, corrosion and stains caused by bacteria, making it easier to keep the products clean and fresh. This not only improves the overall quality and durability of the products, but also reduces the frequency of replacement and maintenance, thereby saving resources and costs.

[0005] In order to overcome the defects of the prior art, the present invention provides an antibacterial regenerated PET elastic fiber and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide an antibacterial regenerated PET elastic fiber and a preparation method thereof, so as to solve the problems in the prior art.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A method for preparing antibacterial regenerated PET elastic fiber comprises the following steps:

[0009] Step 1: dissolving hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolving 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; dropping the aldehyde solution into the hexamethylenediamine solution, stirring and reacting at 70-80° C. for 10-20 hours, filtering after the reaction, removing anhydrous ethanol, separating and purifying to obtain an antibacterial material;

[0010] Step 2: dissolving the antibacterial material in anhydrous ethanol to obtain an antibacterial solution; adding the modified zirconium hydrogen phosphate material to the antibacterial solution, ultrasonically reacting at 30-35° C. for 50-70 hours, filtering, washing, and vacuum drying after the reaction to obtain a modified antibacterial material;

[0011] Step 3: adding the modified antibacterial material to the solvent, ultrasonically dispersing at 25-30°C for 60-80min, adding disodium ethylenediaminetetraacetate, ultrasonically stirring at 40-60°C for 3-5h, adding copper sulfate pentahydrate and continuing to stir and react for 40-60min, adding sodium hydroxide solution and ascorbic acid solution after the reaction, continuing to react for 2-3h, and after the reaction, centrifuging, washing, and vacuum drying to obtain a composite antibacterial material;

[0012] Step 4: crushing the PET waste to obtain recycled PET powder; mixing the recycled PET powder, composite antibacterial material, inorganic pigment, additive and propylene glycol, and subjecting the mixture to high temperature melting, partial cooling, vacuum drying, double helix melting, granulation and melt spinning to obtain PET elastic fiber;

[0013] Step 5: Use the modified solution to ultrasonically pretreat the PET elastic fiber for 3-4 hours, then wash, dry and plasma treat to obtain the pretreated PET elastic fiber; immerse the pretreated PET elastic fiber in the TiO2 solution, react in a 65-70°C water bath for 2-4 hours, wash and dry after the reaction to obtain the finished product.

[0014] More optimally, in step 1, when preparing the antibacterial material, the reaction molar ratio of hexamethylenediamine and 1-methyl-1H-imidazole-2-carbaldehyde is 1:(1.0-1.2).

[0015] More optimally, in step 2, the reaction mass ratio of the antibacterial material and the modified zirconium hydrogen phosphate material is (1.0-1.2):0.5.

[0016] More optimally, the preparation method of the modified zirconium hydrogen phosphate material is as follows: S1: adding phosphorus trichloride to acetophenone, reacting in an ice water bath at 0-5°C for 8-10h, then adding glacial acetic acid and stirring for 10-12h, then adding deionized water and standing for 5-6h, after the reaction is completed, adding concentrated hydrochloric acid after concentration, reflux reaction at 85-95°C for 6-8h, after the reaction is completed, adding toluene after concentration, reflux reaction at 85-95°C for 4-6h, after the reaction is completed, cooling, filtering, washing, and drying to obtain styrylphosphonic acid;

[0017] S2: Add zirconium oxychloride octahydrate and hydrofluoric acid to deionized water, stir thoroughly, then add an aqueous solution of styrylphosphonic acid and sodium dihydrogen phosphate dihydrate, stir and react at 80-85°C for 65-75h. After the reaction is completed, filter, wash with water, wash with alcohol, and dry in vacuum to obtain a modified zirconium hydrogen phosphate material.

[0018] More optimally, the contents of the various components of styrylphosphonic acid are: by volume, 55-60 parts of phosphorus trichloride, 50-55 parts of acetophenone, 80-85 parts of glacial acetic acid, 200-220 parts of concentrated hydrochloric acid, and 100-120 parts of toluene; the contents of the various components of the modified zirconium hydrogen phosphate material are: by mass, 6.5-7.0 parts of zirconium oxychloride octahydrate, 10-12 parts of hydrofluoric acid, 50-70 parts of deionized water, 3.5-4.0 parts of styrylphosphonic acid, and 3.0-3.5 parts of sodium dihydrogen phosphate dihydrate; the mass fraction of the concentrated hydrochloric acid is 36-38%.

[0019] More optimally, in step three, the contents of each component of the composite antibacterial material are: by mass, 2.5-3.0 parts of modified antibacterial material, 2.3-2.5 parts of disodium ethylenediaminetetraacetate, 6.3-6.5 parts of copper sulfate pentahydrate, 6-8 parts of sodium hydroxide, and 1.3-1.5 parts of ascorbic acid; 6-8 parts of sodium hydroxide are dissolved in deionized water to obtain a sodium hydroxide solution; 1.3-1.5 parts of ascorbic acid are dissolved in deionized water to obtain an ascorbic acid solution; the solvent is a mixed solution of ethanol and deionized water, and the volume ratio is (4.5-5.5):1.

[0020] More optimally, in step four, the contents of the components of the PET elastic fiber are: by mass, 100-120 parts of recycled PET powder, 15-20 parts of composite antibacterial materials, 4-6 parts of inorganic pigments, 0.8-1.0 parts of additives, and 8-10 parts of propylene glycol; the inorganic pigment is zinc oxide, and the additive is tetraethyl orthosilicate.

[0021] More optimally, in step 4, the high temperature melting temperature is 290-310°C, the local cooling process is to cool the melt from 290-310°C to 270-280°C, the vacuum drying temperature is 120-140°C; the double helix melting temperature is 270-280°C.

[0022] More optimally, in step five, the modified solution is a mixed solution of ethanol, acetone and deionized water in a volume ratio of 1:1:(1-2); the concentration of the TiO2 solution is 3-4 g / L.

[0023] More optimally, in step five, the plasma treatment parameters are: frequency 50-60 Hz, power 18-20 W, and time 3-5 min.

[0024] Beneficial effects of the present invention:

[0025] The present invention obtains an antibacterial material by adding hexamethylenediamine and 1-methyl-1H-imidazole-2-carboxaldehyde; then the antibacterial material is loaded into a modified zirconium hydrogen phosphate material to obtain a modified antibacterial material; the modified antibacterial material, disodium ethylenediaminetetraacetate, copper sulfate pentahydrate, sodium hydroxide solution and ascorbic acid solution are added to obtain a composite antibacterial material. Recycled PET powder, composite antibacterial material, inorganic pigment, auxiliary agent and propylene glycol are mixed, and PET elastic fiber is obtained through high-temperature melting, local cooling, vacuum drying, double-helix melting, granulation and melt spinning; finally, the PET elastic fiber is impregnated with a TiO2 solution to obtain a finished product.

[0026] The feature of the present invention is that in step 1, a condensation reaction is carried out by adding hexamethylenediamine and 1-methyl-1H-imidazole-2-carboxaldehyde to generate an antibacterial material having a Schiff base structure and an imidazole structure. On the one hand, the Schiff base structure and the imidazole structure obtained in this step can inhibit the synthesis of nucleotides and amino acids, thereby blocking the growth and reproduction of microorganisms, and thus playing a good antibacterial effect; on the other hand, an excess of hexamethylenediamine is added in step 1 of the present invention, so hexamethylenediamine and 1-methyl-1H-imidazole-2-carboxaldehyde can fully react, and there will be residual amine groups in hexamethylenediamine that fail to react completely and remain, and the residual amine groups can fully react with the modified zirconium hydrogen phosphate material in step 2, that is, the P-OH in the modified zirconium hydrogen phosphate material can react with the amine groups to obtain a modified antibacterial material. In step 2, by loading the antibacterial material with residual amine groups into the modified zirconium hydrogen phosphate material with a layered structure, the dispersion performance of the antibacterial material in the recycled PET powder can be effectively improved, thereby ensuring the comprehensive performance of the PET elastic fiber; in addition, the modified zirconium hydrogen phosphate material can also play a good protective effect on the antibacterial material and prevent the antibacterial agent from failing prematurely.

[0027] In step three, a modified antibacterial material, disodium ethylenediaminetetraacetic acid, copper sulfate pentahydrate, sodium hydroxide solution and ascorbic acid solution are added to obtain a composite antibacterial material. This step treats the surface of the modified antibacterial material to obtain a layer of cuprous oxide antibacterial layer, further improving the antibacterial properties of the material, and finally obtaining a composite antibacterial material. The specific mechanism is: the modified antibacterial material and disodium ethylenediaminetetraacetic acid are connected by chelation, thereby introducing carboxyl groups on the surface of the modified antibacterial material, and then the carboxyl groups can adsorb copper ions, and then the copper ions are reduced to obtain a cuprous oxide antibacterial layer.

[0028] In step 4, the PET elastic fiber is surface modified, plasma treated, and impregnated with a TiO2 solution to obtain a finished product. This step is to prepare a layer of TiO2 antibacterial layer on the surface of the already formed PET elastic fiber. By adding the TiO2 antibacterial layer, the PET elastic fiber can be given a stronger antibacterial ability, effectively inhibiting the growth of microorganisms, thereby improving the hygienic properties of the fiber; in addition, the TiO2 antibacterial layer also has the ability to absorb ultraviolet rays, which can provide better ultraviolet protection for the PET elastic fiber, reduce the impact of light aging on the fiber, and extend the service life. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Source of raw materials:

[0031] PET waste is provided by Dongguan Yingtong Recycling Co., Ltd., model number is W151212BG; in terms of volume, 1 part is 1 mL; in terms of mass, 1 part is g.

[0032] Example 1: Step 1: Dissolve 1 mol of hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolve 1 mol of 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; add the aldehyde solution dropwise to the hexamethylenediamine solution, stir and react at 80° C. for 20 hours, and after the reaction is completed, filter, remove anhydrous ethanol, separate and purify to obtain an antibacterial material;

[0033] Step 2: S1: Add 55 mL of phosphorus trichloride to 50 mL of acetophenone, react in an ice-water bath at 5°C for 10 h, then add 80 mL of glacial acetic acid and stir for 12 h, then add deionized water and let stand for 6 h, after the reaction is completed, add 200 mL of 36% concentrated hydrochloric acid after concentration, reflux at 95°C for 8 h, after the reaction is completed, add 100 mL of toluene after concentration, reflux at 95°C for 6 h, after the reaction is completed, cool, filter, wash and dry to obtain styrylphosphonic acid;

[0034] S2: Add 6 g zirconium oxychloride octahydrate and 12 g hydrofluoric acid to 50 g deionized water, stir thoroughly, then add 3.5 g styrylphosphonic acid and 3 g sodium dihydrogen phosphate dihydrate aqueous solution, stir and react at 85° C. for 75 h. After the reaction is completed, filter, wash with water, wash with alcohol, and dry in vacuum to obtain a modified zirconium hydrogen phosphate material;

[0035] S3: dissolving 1 g of the antibacterial material in anhydrous ethanol to obtain an antibacterial solution; adding 0.5 g of the modified zirconium hydrogen phosphate material to the antibacterial solution, subjecting the solution to ultrasonic reaction at 35° C. for 70 h, filtering, washing, and vacuum drying after the reaction to obtain the modified antibacterial material;

[0036] Step 3: dissolve 6g of sodium hydroxide in deionized water to obtain a sodium hydroxide solution; dissolve 1.3g of ascorbic acid in deionized water to obtain an ascorbic acid solution; add 2.5g of the modified antibacterial material to the solvent, ultrasonically disperse at 30°C for 80min, then add 2.3g of disodium ethylenediaminetetraacetate, ultrasonically stir at 60°C for 5h, then add 6.3g of copper sulfate pentahydrate and continue to stir and react for 60min, add sodium hydroxide solution and ascorbic acid solution after the reaction is completed, continue to react for 3h, and after the reaction is completed, centrifuge, wash, and vacuum dry to obtain a composite antibacterial material; the solvent is a mixed solution of ethanol and deionized water in a volume ratio of 5:1;

[0037] Step 4: crushing the PET waste to obtain recycled PET powder; mixing 100g recycled PET powder, 15g composite antibacterial material, 4g zinc oxide, 0.8g ethyl orthosilicate and 8g propylene glycol, and subjecting the mixture to high-temperature melting, local cooling, vacuum drying, double helix melting, granulation and melt spinning to obtain PET elastic fiber; wherein the high-temperature melting temperature is 310°C, the local cooling process is to cool the melt from 310°C to 280°C, the vacuum drying temperature is 140°C; the double helix melting temperature is 280°C;

[0038] Step 5: Use the modified solution to ultrasonically pretreat the PET elastic fiber for 4 hours, then wash, dry and plasma treat to obtain the pretreated PET elastic fiber; the modified solution is a mixed solution of ethanol, acetone and deionized water, and the volume ratio is 1:1:1.5; plasma treatment parameters: frequency is 60Hz, power is 20W, and time is 5min; the pretreated PET elastic fiber is immersed in 3g / L TiO2 solution, reacted in a water bath at 70℃ for 4 hours, and after the reaction is completed, it is washed and dried to obtain the finished product.

[0039] Example 2: Step 1: dissolving 1 mol of hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolving 1 mol of 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; adding the aldehyde solution dropwise to the hexamethylenediamine solution, stirring and reacting at 75° C. for 15 hours, filtering after the reaction, removing anhydrous ethanol, separating and purifying to obtain an antibacterial material;

[0040] Step 2: S1: Add 55 mL of phosphorus trichloride to 50 mL of acetophenone, react in an ice-water bath at 3°C ​​for 9 hours, then add 80 mL of glacial acetic acid and stir for 11 hours, then add deionized water and let stand for 5.5 hours, after the reaction is completed, add 200 mL of 36% concentrated hydrochloric acid after concentration, reflux at 90°C for 7 hours, after the reaction is completed, add 100 mL of toluene after concentration, reflux at 90°C for 5 hours, after the reaction is completed, cool, filter, wash and dry to obtain styrylphosphonic acid;

[0041] S2: Add 6 g zirconium oxychloride octahydrate and 12 g hydrofluoric acid to 50 g deionized water, stir thoroughly, then add 3.5 g styrylphosphonic acid and 3 g sodium dihydrogen phosphate dihydrate aqueous solution, stir and react at 82° C. for 70 h, filter, wash with water, wash with alcohol, and vacuum dry after the reaction to obtain a modified zirconium hydrogen phosphate material;

[0042] S3: dissolving 1 g of the antibacterial material in anhydrous ethanol to obtain an antibacterial solution; adding 0.5 g of the modified zirconium hydrogen phosphate material to the antibacterial solution, subjecting the solution to ultrasonic reaction at 33° C. for 60 h, filtering, washing, and vacuum drying after the reaction to obtain the modified antibacterial material;

[0043] Step 3: dissolve 6g of sodium hydroxide in deionized water to obtain a sodium hydroxide solution; dissolve 1.3g of ascorbic acid in deionized water to obtain an ascorbic acid solution; add 2.5g of the modified antibacterial material to the solvent, ultrasonically disperse at 27°C for 70min, then add 2.3g of disodium ethylenediaminetetraacetate, ultrasonically stir at 50°C for 4h, then add 6.3g of copper sulfate pentahydrate and continue to stir and react for 50min, add sodium hydroxide solution and ascorbic acid solution after the reaction is completed, continue to react for 2.5h, and after the reaction is completed, centrifuge, wash, and vacuum dry to obtain a composite antibacterial material; the solvent is a mixed solution of ethanol and deionized water in a volume ratio of 5:1;

[0044] Step 4: crushing the PET waste to obtain recycled PET powder; mixing 100g recycled PET powder, 15g composite antibacterial material, 4g zinc oxide, 0.8g ethyl orthosilicate and 8g propylene glycol, and subjecting the mixture to high temperature melting, local cooling, vacuum drying, double helix melting, granulation and melt spinning to obtain PET elastic fiber; wherein the high temperature melting temperature is 300°C, the local cooling process is to cool the melt from 300°C to 275°C, the vacuum drying temperature is 130°C; the double helix melting temperature is 275°C;

[0045] Step 5: The PET elastic fiber is ultrasonically pretreated with a modified solution for 3.5 hours, and then washed, dried, and plasma treated to obtain pretreated PET elastic fiber; the modified solution is a mixed solution of ethanol, acetone, and deionized water, and the volume ratio is 1:1:1.5; plasma treatment parameters: frequency is 55 Hz, power is 19 W, and time is 4 min; the pretreated PET elastic fiber is immersed in a 3 g / L TiO2 solution, reacted in a water bath at 67°C for 3 hours, and after the reaction is completed, it is washed and dried to obtain a finished product.

[0046] Example 3: Step 1: dissolving 1 mol of hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolving 1 mol of 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; dropping the aldehyde solution into the hexamethylenediamine solution, stirring and reacting at 70° C. for 10 hours, filtering after the reaction, removing anhydrous ethanol, separating and purifying to obtain an antibacterial material;

[0047] Step 2: S1: Add 55 mL of phosphorus trichloride to 50 mL of acetophenone, react in an ice-water bath at 0°C for 8 h, then add 80 mL of glacial acetic acid and stir for 10 h, then add deionized water and let stand for 5 h, after the reaction is completed, add 200 mL of 36% concentrated hydrochloric acid after concentration, reflux at 85°C for 6 h, after the reaction is completed, add 100 mL of toluene after concentration, reflux at 85°C for 4 h, after the reaction is completed, cool, filter, wash and dry to obtain styrylphosphonic acid;

[0048] S2: Add 6 g zirconium oxychloride octahydrate and 12 g hydrofluoric acid to 50 g deionized water, stir thoroughly, then add 3.5 g styrylphosphonic acid and 3 g sodium dihydrogen phosphate dihydrate aqueous solution, stir and react at 80° C. for 65 h. After the reaction is completed, filter, wash with water, wash with alcohol, and dry in vacuum to obtain a modified zirconium hydrogen phosphate material;

[0049] S3: dissolving 1 g of the antibacterial material in anhydrous ethanol to obtain an antibacterial solution; adding 0.5 g of the modified zirconium hydrogen phosphate material to the antibacterial solution, subjecting the solution to ultrasonic reaction at 30° C. for 50 h, filtering, washing, and vacuum drying after the reaction to obtain the modified antibacterial material;

[0050] Step 3: dissolve 6g of sodium hydroxide in deionized water to obtain a sodium hydroxide solution; dissolve 1.3g of ascorbic acid in deionized water to obtain an ascorbic acid solution; add 2.5g of the modified antibacterial material to the solvent, ultrasonically disperse at 25°C for 60min, then add 2.3g of disodium ethylenediaminetetraacetate, ultrasonically stir at 40°C for 3h, then add 6.3g of copper sulfate pentahydrate and continue to stir and react for 40min, add sodium hydroxide solution and ascorbic acid solution after the reaction is completed, continue to react for 2h, and after the reaction is completed, centrifuge, wash, and vacuum dry to obtain a composite antibacterial material; the solvent is a mixed solution of ethanol and deionized water in a volume ratio of 5:1;

[0051] Step 4: crushing the PET waste to obtain recycled PET powder; mixing 100g recycled PET powder, 15g composite antibacterial material, 4g zinc oxide, 0.8g ethyl orthosilicate and 8g propylene glycol, and subjecting the mixture to high-temperature melting, local cooling, vacuum drying, double helix melting, granulation and melt spinning to obtain PET elastic fiber; wherein the high-temperature melting temperature is 290°C, the local cooling process is to cool the melt from 290°C to 270°C, the vacuum drying temperature is 120°C; the double helix melting temperature is 270°C;

[0052] Step 5: Use the modified solution to ultrasonically pretreat the PET elastic fiber for 3 hours, then wash, dry and plasma treat to obtain the pretreated PET elastic fiber; the modified solution is a mixed solution of ethanol, acetone and deionized water, and the volume ratio is 1:1:1.5; plasma treatment parameters: frequency is 50Hz, power is 18W, and time is 3min; the pretreated PET elastic fiber is immersed in 3g / L TiO2 solution, reacted in a water bath at 65℃ for 2h, and after the reaction is completed, it is washed and dried to obtain the finished product.

[0053] Comparative Example 1: excluding step 5, the rest is the same as Example 1, and the specific steps are as follows: step 1: dissolving 1 mol of hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolving 1 mol of 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; dropping the aldehyde solution into the hexamethylenediamine solution, stirring and reacting at 80° C. for 20 hours, filtering after the reaction, removing anhydrous ethanol, separating and purifying to obtain an antibacterial material;

[0054] Step 2: S1: Add 55 mL of phosphorus trichloride to 50 mL of acetophenone, react in an ice-water bath at 5°C for 10 h, then add 80 mL of glacial acetic acid and stir for 12 h, then add deionized water and let stand for 6 h, after the reaction is completed, add 200 mL of 36% concentrated hydrochloric acid after concentration, reflux at 95°C for 8 h, after the reaction is completed, add 100 mL of toluene after concentration, reflux at 95°C for 6 h, after the reaction is completed, cool, filter, wash and dry to obtain styrylphosphonic acid;

[0055] S2: Add 6 g zirconium oxychloride octahydrate and 12 g hydrofluoric acid to 50 g deionized water, stir thoroughly, then add 3.5 g styrylphosphonic acid and 3 g sodium dihydrogen phosphate dihydrate aqueous solution, stir and react at 85° C. for 75 h. After the reaction is completed, filter, wash with water, wash with alcohol, and dry in vacuum to obtain a modified zirconium hydrogen phosphate material;

[0056] S3: dissolving 1 g of the antibacterial material in anhydrous ethanol to obtain an antibacterial solution; adding 0.5 g of the modified zirconium hydrogen phosphate material to the antibacterial solution, subjecting the solution to ultrasonic reaction at 35° C. for 70 h, filtering, washing, and vacuum drying after the reaction to obtain the modified antibacterial material;

[0057] Step 3: dissolve 6g of sodium hydroxide in deionized water to obtain a sodium hydroxide solution; dissolve 1.3g of ascorbic acid in deionized water to obtain an ascorbic acid solution; add 2.5g of the modified antibacterial material to the solvent, ultrasonically disperse at 30°C for 80min, then add 2.3g of disodium ethylenediaminetetraacetate, ultrasonically stir at 60°C for 5h, then add 6.3g of copper sulfate pentahydrate and continue to stir and react for 60min, add sodium hydroxide solution and ascorbic acid solution after the reaction is completed, continue to react for 3h, and after the reaction is completed, centrifuge, wash, and vacuum dry to obtain a composite antibacterial material; the solvent is a mixed solution of ethanol and deionized water in a volume ratio of 5:1;

[0058] Step 4: Crush the PET waste to obtain recycled PET powder; mix 100g recycled PET powder, 15g composite antibacterial material, 4g zinc oxide, 0.8g tetraethyl orthosilicate and 8g propylene glycol, and obtain the finished product through high-temperature melting, local cooling, vacuum drying, double helix melting, granulation and melt spinning; wherein the high-temperature melting temperature is 310°C, the local cooling process is to cool the melt from 310°C to 280°C, the vacuum drying temperature is 140°C; the double helix melting temperature is 280°C.

[0059] Comparative Example 2: Step 2 and Step 3 are removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: Dissolve 1 mol of hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolve 1 mol of 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; add the aldehyde solution dropwise to the hexamethylenediamine solution, stir and react at 80° C. for 20 hours, and after the reaction, filter, remove anhydrous ethanol, separate and purify to obtain an antibacterial material;

[0060] Step 2: pulverize the PET waste to obtain recycled PET powder; mix 100g recycled PET powder, 15g antibacterial material, 4g zinc oxide, 0.8g ethyl orthosilicate and 8g propylene glycol, and obtain PET elastic fiber through high-temperature melting, local cooling, vacuum drying, double helix melting, granulation, and melt spinning; wherein the high-temperature melting temperature is 310°C, the local cooling process is to cool the melt from 310°C to 280°C, the vacuum drying temperature is 140°C; the double helix melting temperature is 280°C;

[0061] Step three: Use the modified solution to ultrasonically pretreat the PET elastic fiber for 4 hours, then wash, dry and plasma treat to obtain the pretreated PET elastic fiber; the modified solution is a mixed solution of ethanol, acetone and deionized water, and the volume ratio is 1:1:1.5; plasma treatment parameters: frequency is 60Hz, power is 20W, and time is 5min; the pretreated PET elastic fiber is immersed in 3g / L TiO2 solution, reacted in a water bath at 70℃ for 4 hours, and after the reaction is completed, it is washed and dried to obtain the finished product.

[0062] Comparative Example 3: Step 1, step 2 and step 3 are removed, and the rest is the same as Example 1, and the specific steps are as follows: Step 1: PET waste is crushed to obtain recycled PET powder; 100g recycled PET powder, 4g zinc oxide, 0.8g tetraethyl orthosilicate and 8g propylene glycol are mixed, and PET elastic fiber is obtained by high-temperature melting, local cooling, vacuum drying, double helix melting, granulation, and melt spinning; wherein the high-temperature melting temperature is 310°C, the local cooling process is to cool the melt from 310°C to 280°C, and the vacuum drying temperature is 140°C; the double helix melting temperature is 280°C;

[0063] Step 2: Use a modified solution to ultrasonically pretreat the PET elastic fiber for 4 hours, then wash, dry, and plasma treat to obtain pretreated PET elastic fiber; the modified solution is a mixed solution of ethanol, acetone, and deionized water in a volume ratio of 1:1:1.5; plasma treatment parameters: frequency of 60 Hz, power of 20 W, time of 5 minutes; the pretreated PET elastic fiber is immersed in a 3 g / L TiO2 solution, reacted in a 70°C water bath for 4 hours, and after the reaction is completed, it is washed and dried to obtain a finished product.

[0064] Detection test:

[0065] Antibacterial performance test: The finished product prepared by the present invention is used as a sample, and the antibacterial performance of the sample is tested according to standard FZ / T73023-2006, and the test bacteria are Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli. First, the bacterial solution is cultured at 37°C for 25 hours, and then the cultured bacterial solution is inoculated on the sample, and oscillated for 18 hours at a temperature of 24°C and a rotation speed of 150r / min; then the bacterial solution is diluted and inoculated into a nutrient agar medium, and cultured at 37°C for 24 hours; finally, the antibacterial rate is calculated according to the formula.

[0066] Mechanical property test: The finished product prepared by the present invention is used as a sample, and the fracture strength of the sample is tested according to GB / T 14337-2008 standard. The results are shown in the following table:

[0067] Antibacterial rate / % <![CDATA[Tensile strength / (N / dtex )]]> Example 1 93 3.7 Example 2 92 3.6 Example 3 92 3.6 Comparative Example 1 88 3.6 Comparative Example 2 84 3.3 Comparative Example 3 79 3.6

[0068] Conclusion: The dosage of Examples 1 to 3 remains unchanged, and only some reaction parameters are modified. From the experimental data, it can be seen that there is no obvious fluctuation in the performance of the samples.

[0069] Comparative Example 1: Step 5 is removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate is reduced to 88%, and the breaking strength is reduced to 3.6N / dtex. The reason is analyzed as follows: after step 5 is removed, the surface of the PET elastic fiber is not impregnated with TiO2 solution, which will reduce the antibacterial performance of the sample compared with Example 1, so the antibacterial rate is reduced.

[0070] Comparative Example 2: Steps 2 and 3 are removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate is reduced to 84%, and the breaking strength is reduced to 3.3N / dtex. The reasons are analyzed as follows: after removing steps 2 and 3, compared with Example 1, in Comparative Example 2, the antibacterial material and other additives are directly added to the recycled PET powder, which will reduce the mechanical properties of the sample, and thus the breaking strength is reduced; in addition, after removing step 3, the cuprous oxide antibacterial layer will also be removed, so the antibacterial performance is reduced and the antibacterial rate is reduced.

[0071] Comparative Example 3: Step 1, Step 2 and Step 3 are removed, and the rest is the same as Example 1. It can be seen from the experimental data that compared with Example 1, the antibacterial rate is reduced to 79%, and the breaking strength is reduced to 3.6N / dtex. The reason is analyzed as follows: after removing Step 1, Step 2 and Step 3, the antibacterial components of the sample are significantly reduced, so the antibacterial performance will be significantly reduced, and the antibacterial rate is reduced.

[0072] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0073] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing antibacterial regenerated PET elastic fiber, characterized in that: The following steps are involved: Step 1: dissolving hexamethylenediamine in anhydrous ethanol to obtain a hexamethylenediamine solution; dissolving 1-methyl-1H-imidazole-2-carboxaldehyde in anhydrous ethanol to obtain an aldehyde solution; dropping the aldehyde solution into the hexamethylenediamine solution, stirring and reacting at 70-80° C. for 10-20 hours, filtering after the reaction, removing anhydrous ethanol, separating and purifying to obtain an antibacterial material; Step 2: dissolving the antibacterial material in anhydrous ethanol to obtain an antibacterial solution; adding the modified zirconium hydrogen phosphate material to the antibacterial solution, ultrasonically reacting at 30-35° C. for 50-70 hours, filtering, washing, and vacuum drying after the reaction to obtain a modified antibacterial material; Step 3: adding the modified antibacterial material to the solvent, ultrasonically dispersing at 25-30°C for 60-80min, adding disodium ethylenediaminetetraacetate, ultrasonically stirring at 40-60°C for 3-5h, adding copper sulfate pentahydrate and continuing to stir and react for 40-60min, adding sodium hydroxide solution and ascorbic acid solution after the reaction, continuing to react for 2-3h, and after the reaction, centrifuging, washing, and vacuum drying to obtain a composite antibacterial material; Step 4: crushing the PET waste to obtain recycled PET powder; mixing the recycled PET powder, composite antibacterial material, inorganic pigment, additive and propylene glycol, and subjecting the mixture to high temperature melting, partial cooling, vacuum drying, double helix melting, granulation and melt spinning to obtain PET elastic fiber; Step 5: The PET elastic fiber is subjected to ultrasonic pretreatment for 3-4 hours using the modified solution, and then washed, dried, and plasma treated to obtain the pretreated PET elastic fiber; The pretreated PET elastic fiber is immersed in the TiO2 solution, reacted in a water bath at 65-70°C for 2-4 hours, and after the reaction is completed, it is washed and dried to obtain a finished product.

2. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step 1, when preparing the antibacterial material, the reaction molar ratio of hexamethylenediamine and 1-methyl-1H-imidazole-2-carboxaldehyde is 1:(1.0-1.2).

3. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step 2, the reaction mass ratio of the antibacterial material and the modified zirconium hydrogen phosphate material is (1.0-1.2):0.

5.

4. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 3, characterized in that: The preparation method of the modified zirconium hydrogen phosphate material is as follows: S1: adding phosphorus trichloride to acetophenone, reacting in an ice water bath at 0-5°C for 8-10h, then adding glacial acetic acid and stirring for 10-12h, then adding deionized water and standing for 5-6h, after the reaction is completed, concentrated hydrochloric acid is added, and reflux reaction is carried out at 85-95°C for 6-8h, after the reaction is completed, toluene is added after concentration, and reflux reaction is carried out at 85-95°C for 4-6h, after the reaction is completed, the reaction is cooled, filtered, washed, and dried to obtain styrylphosphonic acid S2: Add zirconium oxychloride octahydrate and hydrofluoric acid to deionized water, stir thoroughly, then add an aqueous solution of styrylphosphonic acid and sodium dihydrogen phosphate dihydrate, stir and react at 80-85°C for 65-75h. After the reaction is completed, filter, wash with water, wash with alcohol, and dry in vacuum to obtain a modified zirconium hydrogen phosphate material.

5. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 4, characterized in that: The contents of the components of styrylphosphonic acid are as follows: by volume, 55-60 parts of phosphorus trichloride, 50-55 parts of acetophenone, 80-85 parts of glacial acetic acid, 200-220 parts of concentrated hydrochloric acid, and 100-120 parts of toluene; the contents of the components of the modified zirconium hydrogen phosphate material are as follows: by mass, 6.5-7.0 parts of zirconium oxychloride octahydrate, 10-12 parts of hydrofluoric acid, 50-70 parts of deionized water, 3.5-4.0 parts of styrylphosphonic acid, and 3.0-3.5 parts of sodium dihydrogen phosphate dihydrate; and the mass fraction of the concentrated hydrochloric acid is 36-38%.

6. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step three, the contents of each component of the composite antibacterial material are: by mass, 2.5-3.0 parts of modified antibacterial material, 2.3-2.5 parts of disodium ethylenediaminetetraacetate, 6.3-6.5 parts of copper sulfate pentahydrate, 6-8 parts of sodium hydroxide, and 1.3-1.5 parts of ascorbic acid; 6-8 parts of sodium hydroxide are dissolved in deionized water to obtain a sodium hydroxide solution; 1.3-1.5 parts of ascorbic acid are dissolved in deionized water to obtain an ascorbic acid solution; the solvent is a mixed solution of ethanol and deionized water, and the volume ratio is (4.5-5.5):

1.

7. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step 4, the contents of the components of the PET elastic fiber are: by mass, 100-120 parts of recycled PET powder, 15-20 parts of composite antibacterial materials, 4-6 parts of inorganic pigments, 0.8-1.0 parts of additives, and 8-10 parts of propylene glycol; the inorganic pigment is zinc oxide, and the additive is tetraethyl orthosilicate.

8. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step 4, the high temperature melting temperature is 290-310°C, the local cooling process is to cool the melt from 290-310°C to 270-280°C, the vacuum drying temperature is 120-140°C; the double helix melting temperature is 270-280°C.

9. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step five, the modified solution is a mixed solution of ethanol, acetone and deionized water in a volume ratio of 1:1:(1-2); the concentration of the TiO2 solution is 3-4 g / L.

10. The method for preparing an antibacterial regenerated PET elastic fiber according to claim 1, characterized in that: In step 5, the plasma treatment parameters are: frequency is 50-60 Hz, power is 18-20 W, and time is 3-5 min.

Citation Information

Patent Citations

  • Manufacturing technology for dust-proof and antibacterial sportswear shell fabric

    CN111764025A

  • Nano zirconium phosphate-based flame-retardant bacteriostatic agent, and intumescent fireproof bacteriostatic coating prepared therefrom

    CN113861794A

  • Efficient antibacterial polyethylene glycol terephthalate composite material and preparation method thereof

    CN115521592A